2014
DOI: 10.1002/ajmg.b.32205
|View full text |Cite
|
Sign up to set email alerts
|

A variant within FGF1 is associated with Alzheimer's disease in the Han Chinese population

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder characterized by the accumulation of amyloid beta (Aβ) plaques and Tau-containing neurofibrillary tangles in vulnerable brain areas. The progression of AD is well correlated with hippocampal neuron loss which highly suggests genes associated with neuron survival would be important for AD pathogenesis. According to the recent results of genome-wide association studies (GWAS) and other reported studies, we selected two single nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In addition to our findings, dysregulation of H4K12 acetylation is involved in age-associated memory loss (Peleg et al, 2010). FGF1 may be involved in the pathophysiology of Alzheimer’s disease (Lou et al, 2012; Tao et al, 2014; Yamagata et al, 2004) and recombinant FGFs have been used to treat multiple disorders (Beenken and Mohammadi, 2009). Therefore, Fgf1b and the components of its transcriptional machinery may be a target for cognitive enhancement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our findings, dysregulation of H4K12 acetylation is involved in age-associated memory loss (Peleg et al, 2010). FGF1 may be involved in the pathophysiology of Alzheimer’s disease (Lou et al, 2012; Tao et al, 2014; Yamagata et al, 2004) and recombinant FGFs have been used to treat multiple disorders (Beenken and Mohammadi, 2009). Therefore, Fgf1b and the components of its transcriptional machinery may be a target for cognitive enhancement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…FGF‐1 promotes the survival of neurons, and it was reported that serum FGF‐1 in patients with AD was higher than in patients without AD . It was also reported that variants within FGF‐1 were associated with AD in Chinese Han population . The ADRA1A gene located on chromosome 8 has been selected 15%, and only the additive effects have been selected.…”
Section: Real‐data Applicationmentioning
confidence: 99%
“…50 It was also reported that variants within FGF-1 were associated with AD in Chinese Han population. 51 The ADRA1A gene located on chromosome 8 has been selected 15%, and only the additive effects have been selected. It has been shown that mutations in ADRA1A can lead to early onset of AD.…”
Section: Accuracy Comparisons For Fdgmentioning
confidence: 99%
“…In addition to CRTC1, there are also reports suggesting a possible role of FGF1 in Alzheimer’s disease. Genetic studies indicate significant association of single nucleotide polymorphisms (SNPs) within the FGF1 gene (Tao et al, 2014; Yamagata et al, 2004). In addition, the number of FGF1-immunolabeled neurons is reduced in patients with Alzheimer’s disease (Thorns et al, 2001; Thorns and Masliah, 1999).…”
Section: Possible Involvement Of Crtc1 and Fgf1 In Memory-related Dismentioning
confidence: 99%